Case report: A rare case of desmoid-type fibromatosis originating in the small intestine - Xie, Junfeng; Lai, Shichang; Wang, Yangbiao; Ye, Baolong; Huang, Zhishun; Xi, Kexing (Frontiers in Medicine, 2023)
Background: Desmoid-type fibromatosis (DF) is characterized by a rare monoclonal fibroblast proliferation that exhibits variable and unpredictable clinical presentation. DF can be classified into sporadic and hereditary types. Despite extensive research efforts, the exact etiology of DF remains elusive.Case Description: A 31-year-old male patient presented to the hospital with a progressively growing mass in the right lower abdomen, accompanied by abdominal discomfort. Symptoms are discovered one week before admission. Enteroscopy revealed no evidence of colonic abnormalities, and blood tests did not indicate any abnormalities. Due to the indeterminate nature of the mass during surgery, a partial resection of the ileum and cecum was performed, followed by ileocolonic end-to-end anastomosis, with no postoperative complications. The final pathological diagnosis confirmed primary desmoid-type fibromatosis of the distal ileum (invasive fibromatosis). To effectively manage DF, we recommend a follow-up schedule for patients. This includes appointments every three months in the first year following surgery, followed by appointments every six months up to the fifth year, and then once a year thereafter. The follow-up examinations should include collection of the patient's medical history, physical examination, blood tests, ultrasounds, CT scans, and other relevant assessments. During the first year of the follow-up period, no further treatment was administered, and the patient remained disease-free.Conclusions: Desmoid-type fibromatosis (DF) originating from the small intestine is an extremely rare condition that exhibits local invasiveness and can be life-threatening. Despite its benign histology, DF has a high local recurrence rate and lacks metastatic potential. Diagnosis of DF remains challenging, especially in cases where surgical intervention is not feasible due to asymptomatic patients or partial organ impairment. In such cases, a "watchful waiting" approach is recommended as the initial treatment strategy. However, when preoperative diagnosis is difficult, surgery is typically considered the best option. Given the potential for local recurrence and the uncertain long-term prognosis, regular follow-up is necessary.